2016
DOI: 10.2106/jbjs.15.00702
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and Complications After Open Versus Posterior Arthroscopic Subtalar Arthrodesis in 121 Patients

Abstract: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
74
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(80 citation statements)
references
References 28 publications
5
74
1
Order By: Relevance
“…We report an overall rate of successful union of 97.4%, which is comparable to previously published results for both arthroscopic [5,12,[14][15][16][17][18][19][20][21][22][23][24][25] and open [1][2][3][4][5]11] subtalar arthrodesis. The low incidence of surgical site infection and nerve injury in our series are favourable to rates reported for open arthrodesis [1][2][3], and comparable to those previously seen in arthroscopic subtalar arthrodesis.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…We report an overall rate of successful union of 97.4%, which is comparable to previously published results for both arthroscopic [5,12,[14][15][16][17][18][19][20][21][22][23][24][25] and open [1][2][3][4][5]11] subtalar arthrodesis. The low incidence of surgical site infection and nerve injury in our series are favourable to rates reported for open arthrodesis [1][2][3], and comparable to those previously seen in arthroscopic subtalar arthrodesis.…”
Section: Discussionsupporting
confidence: 87%
“…with several studies suggesting benefits over open arthrodesis in terms of union time, functional outcome, length of inpatient stay, and blood loss [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These fusion conditions thus seemed not to influence the fusion ratio in the present series. Rungprai et al (2016) [11], at last follow-up of arthroscopic posterior subtalar fusion, reported a 5.1 point gain in pain VAS, and 24.5 and 17 point gains in SF-36 physical and mental component scores respectively. Other authors likewise reported mean AOFAS score gains ranging between 31 and 50 points [4,5,8].…”
Section: Discussionmentioning
confidence: 99%
“…Technological progress and surgeons' improved arthroscopic skill have opened a field of possibilities to reduce morbidity following subtalar fusion. Fusion times and rates seem to be better with arthroscopic techniques, although there remains some disagreement [3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%